2001
DOI: 10.1034/j.1399-0012.2001.150510.x
|View full text |Cite
|
Sign up to set email alerts
|

The hepatic artery in liver transplantation and surgery: vascular anomalies in 701 cases

Abstract: The purpose of this study is to report the variations in hepatic arterial supply of a mixed population of organ donors in which the anatomy was individually examined during the bench surgery, and patients who underwent a selective angiogram of the celiac axis and superior mesenteric artery. We reviewed the donor forms and/or angiograms of 701 patients. The donor forms were completed personally by one of the authors, while all the radiology images were obtained through studies performed by one single radiologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 8 publications
5
82
1
1
Order By: Relevance
“…[3][4][5]8,10,12 Michels 3 reported in 1966 a classification of 10 possible anatomical variants of the extrahepatic arterial distribution that was based on a study of 200 autopsy cases. After Michels 3 initial classification, several authors described their own observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5]8,10,12 Michels 3 reported in 1966 a classification of 10 possible anatomical variants of the extrahepatic arterial distribution that was based on a study of 200 autopsy cases. After Michels 3 initial classification, several authors described their own observations.…”
Section: Discussionmentioning
confidence: 99%
“…These studies are based on angiographic data and autopsy dissections, and mainly derive from surgery and transplantation literature. [4][5][6][7][8][9][10][11][12][13][14] The large sample size of transplanted livers is one of the major interests of this study. Indeed, harvested livers offer an excellent opportunity to describe, in situ, the anatomic variants of the arteries since all extrahepatic arteries need to be carefully identified during this step of the liver transplantation procedure to avoid injuries that jeopardize the viability of the graft once implanted.…”
mentioning
confidence: 99%
“…[10][11][12] In contrast to clinical studies, anatomic studies show a considerably higher frequency of anatomic variants, with a rate between 40% and 75%. [13][14][15] However, this difference between clinical and autopsy studies, observed throughout decades, can possibly be explained by the fact that most anatomic variants may not be detected during the surgical procedure or are considered to be clinically irrelevant and therefore not documented. To avoid accidental transsection of small accessory arteries, we emphasize careful preparation of the minor omentum and palpation or even surgical identification of the hepatic artery in the ligamentum hepatoduodenale before cold perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The respective incidence in our population was consistent with that reported in the literature. [6][7][8] Of equal representation, 2 (2.1%) donors had a replaced CHA, replaced LHA from the GDA, and a common origin of the CA and the superior mesenteric artery. The remaining 10 (10.5%) patients had unique aberrant anatomy.…”
Section: Resultsmentioning
confidence: 99%